Implementation of communication equilibria by correlated cheap talk: The two-player case - Françoise Forges; Péter Vida (Theoretical Economics, 2013)
We show that essentially every communication equilibrium of any finite Bayesian game with two players can be implemented as a strategic form correlated equilibrium of an extended game, in which before choosing actions as in the Bayesian game, the players engage in a possibly infinitely long (but in equilibrium almost surely finite), direct, cheap talk.
Keywords: C72; D70; 330; Bayesian game; cheap talk; communication equilibrium; correlated equilibrium; pre-play communication